Constructing the Image of Muhammad in Europe - Di Cesare, Michelina; Coffey, Heather; Saviello, Alberto (De Gruyter, 2013)
The volume represents a significant contribution to the complex history of the conceptualization and pictorialization of the Prophet Muhammad in the West. It gives a rapid and though deep overview of the history of the making of an image of the Prophet Muhammad in Europe and thus reflects the whole history of the making of the image of Islam in the Latin West, from the early medieval times till the 19th century. The book also provides the reader with ready access to the most recent scholarship concerning the image of Muhammad in Europe, in the form of comprehensive footnotes provided throughout the text and an extensive bibliography.